2017
DOI: 10.1002/adv.21878
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of starch nanocomposite embedded with functionalized MWCNT: Investigation of optical, morphological, thermal, and copper ions adsorption properties

Abstract: The purpose of this research was to fabricate starch nanocomposites (NC)s using corn starch and MWCNTs-Valine as efficient fillers, and to examine the impact of nanofillers on the starch's properties. At first, Valine was grafted onto the MWCNTs' surfaces through a chemical reaction. Then, the functionalized MWCNTs (0.5, 1, and 2 wt.%) were embedded in the starch by ultrasonic technique. The field emission scanning electron microscopy showed homogeneous distribution of nanofillers in the starch matrix. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Zhang et al [ 10 ] and Tian et al [ 11 ] have reported that ultrasound can improve the ability of starch to include small molecules. Furthermore, the use of ultrasonication for the preparation of inclusions is a well–established method [ 12 , 13 , 14 ]. Moreover, not only does the ultrasonication process promote mass transfer, but suitable ultrasonication conditions do not change the crystalline types of the starch [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 10 ] and Tian et al [ 11 ] have reported that ultrasound can improve the ability of starch to include small molecules. Furthermore, the use of ultrasonication for the preparation of inclusions is a well–established method [ 12 , 13 , 14 ]. Moreover, not only does the ultrasonication process promote mass transfer, but suitable ultrasonication conditions do not change the crystalline types of the starch [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amylose or poly-α-1, 4-D-glucan molecule is primarily a linear construction of α-1,4 connected glucose parts. On the other hand, amylopectin or poly-α-1,4-D-glucan and α-1,6-D-glucan are a branched construction made by short α-1,4 parts connected by α-1,6 bonds [11]. In this work, starch due to having large number of hydroxyl end-groups and being naturally abundant, was selected as a functionalization agent for magnetite and such structure would be able to improve the biosorption capacity of the Sr(II).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a sudden increase in conductivity occurs for these composites in a relatively narrow concentration range for the so-called percolation threshold of the filler [3]. Recently, polymers prepared from renewable resources as matrices for solid conducting composites, including starch [4][5][6][7][8][9][10][11][12], cellulose [13], pectin [14], and chitosan [15], have been investigated.…”
Section: Introductionmentioning
confidence: 99%